Predictive value of skill performance in terms of physical indicators in 14-year-old football players - Al Jaleel Abd Al Zahra, Mahmood Abd; Hadi, Ali Kadhim; Saad , Ahmed Khattar (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The primary objective of this study was to identify the reality of the physical fitness and skills among young football players in the Najaf Governorate and to find a predictive value for the physical and skills indicators for the selection of junior football players in Najaf Governorate. The researchers used the descriptive approach with two methods of interrelationships. The present study was conducted on the 14 years old players of football schools in Najaf Governorate in the year 2021. The study was conducted in the playgrounds of the football school in the center of Najaf Governorate (Iraq) within the timeframe from January 2021 to March 2021. A total of 40 14-year-old football players participated in the study. Based on the findings of this study, the researchers concluded that the physical fitness of the football players is directly and significantly related to their skill performance.